Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Keputusan Pembelian Produk iPhone - Harris, Rizki Maulana; Silvianita, Anita (SAFE-Network, 2023)
In an increasingly digitally connected world, technology products such as the iPhone have become a popular choice among consumers; Service quality and customer satisfaction play an important role in consumer purchasing decisions. The research method used is a survey distributed to participants who are iPhone product users. The collected data were analyzed using regression analysis and descriptive statistics to evaluate how the studied variables relate to one another. This study aims to analyze the effect of service quality and customer satisfaction on purchasing decisions for Iphone products. The number in this study are customers who use Iphone products with a total of 100 respondents. Based on the results of the study indicate that service quality has a positive and significant effect on purchasing decisions. Consumer trust has a positive and significant effect on purchasing decisions. Service quality and consumer trust have a positive and significant effect on purchasing decisions. Better understanding of how service quality and customer satisfaction influence consumer decisions to buy iPhone products allows companies to develop more efficient marketing strategies and increase customer loyalty. Further research can be conducted to explore other components that can influence consumer purchasing decisions for technology products.